DEVELOPMENT OF INTERACTIVE MONOPOLY GAME LEARNING MEDIA BASED ON ZEP QUIZ TO INCREASE LEARNING MOTIVATION OF GRADE X SMK STUDENTS: Pengembangan Media Pembelajaran Game Interaktif Monopoli Berbasis Zep Quiz Untuk Meningkatkan Motivasi Belajar Siswa Kelas X SMK - Ria Lailiyah; Aulia Fitriany; M. Khusni Mubarok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to develop an interactive history learning medium based on Zep Quiz and to determine its effectiveness in enhancing student learning motivation. The study employed the DDR (Didactical Design Research) model, comprising the stages of analysis, Design, development, implementation, and evaluation. The research participants were students from class X TKJ 1. The average score on the learning motivation questionnaire was 80.86. Data analysis using the One-Sample Kolmogorov-Smirnov test on residual normality yielded an Asymp. Sig. (2-tailed) value of 0.200, which exceeds the significance level of 0.05. Additionally, the Monte Carlo Sig. value of 0.764 was also greater than 0.05. The Zep Quiz medium contributed 79.4% to student learning motivation. The calculated t-value (11.290) exceeded the t-table value (2.035), and the p-value (<0.001) was less than 0.05; consequently, the null hypothesis (H0) was rejected. Partial analysis indicated that the Zep Quiz learning medium influenced student learning motivation. Based on these findings, it is concluded that the use of the Zep Quiz-based learning medium is effective for enhancing student learning motivation and fostering a technology-based, interactive learning process, particularly in history lessons.